Microbial hyaluronic acid production: a review - Serra, Mónica (2023)
Microbial production of hyaluronic acid (HA) is an area of research that has been gaining attention in recent years due to the increasing demand for this biopolymer for several industrial applications. Hyaluronic acid is a linear, non-sulfated glycosaminoglycan that is widely distributed in nature and is mainly composed of repeating units of N-acetylglucosamine and glucuronic acid. It has a wide and unique range of properties such as viscoelasticity, lubrication, and hydration, which makes it an attractive material for several industrial applications such as cosmetics, pharmaceuticals, and medical devices. This review presents and discusses the available fermentation strategies to produce hyaluronic acid.